Geometric phase for spherical magnetic particles - Körpınar, Talat; Sazak, Ahmet (Elsevier GmbH, 2023)
In this study, we study on the characterization of the behavior of a dynamically charged magnetic particle in spherical space and on the geometrical expressions of electromagnetic parameters resulting from this behavior in spherical space. First, we characterize the spherical-magnetic particles and spherical-magnetic fields, which we named associated with the spherical frame. Then, with the help of the Lorentzian force and the Newtonian force relationship, we obtain the electric field of these magnetic particles in terms of the particle's charge and mass. Next, with the help of electric field and magnetic field, we obtain important electromagnetic parameters such as energy density, power flow, light intensity and power of these spherical magnetic particles. Finally, we obtain the geometric (Berry) phases formed by Heisenberg antiferromagnetic models of the power flows. © 2022 Elsevier GmbH
Keywords: Antiferromagnetic model; Berry phase; Electromagnetism; Energy density; Geometric phase; Power flow; Antiferromagnetism; Electric fields; Electric load flow; Fruits; Spheres; Antiferromagnetic models; Berry's phase; Electromagnetic parameters; Energy density; Geometric phase; Magnetic particle; Magnetic-field; Newtonian forces; Power flows; Spherical space; Magnetic fields